Nicotinamide Mononucleotide: A Promising Molecule for Therapy of Diverse Diseases by Targeting NAD+ Metabolism - Hong, Weiqi; Mo, Fei; Zhang, Ziqi; Huang, Mengyuan; Wei, Xiawei (Frontiers in Cell and Developmental Biology, 2020)
NAD+, a co-enzyme involved in great deal of biochemical reactions, has been found to be a network node of diverse biological processes. In mammalian cells, NAD+ is synthetized, predominantly through NMN, to replenish the consumption by NADase participating in physiologic processes including DNA repair, metabolism and cell death. Correspondingly, aberrant of NAD+ metabolism is observed in many diseases. In this review, we discuss how the homeostasis of NAD+ is maintained in healthy condition and provide several age-related pathological examples related with NAD+ unbalance. The sirtuins family, whose functions are NAD-dependent is also reviewed. Administration of NMN surprisingly demonstrated amelioration of the pathological conditions in some age-related disease mouse models. Further clinical trials have been launched to investigate the safety and benefits of NMN. The NAD+ production and consumption pathways including NMN are essential for more precise understanding and therapy of age-related pathological processes such as diabetes, ischemia-reperfusion injury, heart failure, Alzheimer's disease and retinal degeneration.